A CENTURIAL ANALYSIS OF RAINFALL VARIABILITY IN NIGERIA (Nigerian Journal of Technology, 2018)
This paper examines rainfall variability in Nigeria using monthly rainfall data from 1901 to 2012. This is necessary for planning and management of agriculture and water resource systems. Data for the study were retrieved from the portal archives of World Bank Climate Change Knowledge. Descriptive statistics, trend analysis, and seasonality index were employed in the study. Fluctuations across the months and years were respectively examined through MAKESENS® statistics and Seasonality Index. The result revealed minimum and maximum amounts of rainfall in January and August respectively. The Z and Q statistics indicate an upward trend and positive slope respectively but the null hypothesis of no trend is accepted only in November, December and January due to very low amount of rainfall. The highest maximum and minimum amount of rainfall occurred in July and August while the lowest maximum and minimum both took place in January but the years in which these sets of maximums and minimums happened each followed a zigzag pattern which connotes fluctuations in the amount of rainfall. The maximum, minimum and average seasonality indexes are 0.924, 0.706 and 0.779 respectively, which indicate seasonal and markedly seasonal with a long dry season. There is the need to harvest, store and treat excess water during the wet months for use in dry months. The study recommends that the ministry of water resources should adopt best practices to provide water for Nigerians during the long dry months.  http://dx.doi.org/10.4314/njt.v37i2.34